1988
DOI: 10.1002/j.2161-4296.1988.tb00974.x
|View full text |Cite
|
Sign up to set email alerts
|

Aiding GPS with Calibrated Loran-C

Abstract: GPS is currently being installed; when it is operational, five satellites will be in view virtually 100 percent of the time. However, the full constellation will not be in place for several years, and even then satellite failures may introduce coverage holes. Additionally, even with the full constellation, a GPS receiver will not always be able to monitor signal integrity unless some external aid is used. Loran‐C can be used effectively to aid GPS. A hybrid receiver can combine Loran lines of position with GPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Other signals have less influence on it. 4), and CE-OFDM-PM (8). Obviously, the SSC of our proposed scheme and the above-listed modulation is significantly smaller than that of other spread spectrum signals.…”
Section: • Compatibilitymentioning
confidence: 88%
See 3 more Smart Citations
“…Other signals have less influence on it. 4), and CE-OFDM-PM (8). Obviously, the SSC of our proposed scheme and the above-listed modulation is significantly smaller than that of other spread spectrum signals.…”
Section: • Compatibilitymentioning
confidence: 88%
“…Obviously, the SSC of our proposed scheme and the above-listed modulation is significantly smaller than that of other spread spectrum signals. Except for CE-OFDM-PM (4) and CE-OFDM-PM (8), which shows that our proposed scheme can easily be compatible with service signals of the same frequency band, while their own compatibility is also remarkable. • Anti-multipath Figure 14 shows the multipath error envelope of different spread spectrum-modulated signals under the condition of multipath delay within 500 m. It can be clearly seen from the envelope line that the solution proposed in this paper (marked by the grey dashed line) is a multipath error and is significantly smaller than that of several other types of spread spectrum-modulated signals, which means that the proposed scheme has a better anti-multipath performance when there are short-distance multipath delays.…”
Section: • Compatibilitymentioning
confidence: 89%
See 2 more Smart Citations
“…Recent developments in Loran-C practice have resulted in very low residual effects due to land paths. Enge and McCullough 9 have shown that imperfectly-mapped conductivity variations and modelling errors result in small systematic discrepancies in the ASF values calculated. These discrepancies can generally be substantially eliminated, and certainly reduced to the order of the minimum random errors of the system, by adjusting the results of the conductivity model to give an optimum fit with a sparse set of survey measurements.…”
Section: P R O P a G A T I O N Over Land Pathsmentioning
confidence: 99%